Pendidikan Kesehatan Perilaku Hidup Bersih Dan Sehat Dengan Media Booklet Serta Pemeriksaan Gula Darah Sewaktu Di Pasar Tradisional Desa Adat Mengwi Kecamatan Mengwi Kabupaten Badung - Suyasa, I Nyoman Gede; Jirna, I Nyoman (Jurnal Pengabmas Masyarakat Sehat, 2024)
Clean and healthy living behavior in the market environment has a very important role in the health of the market, starting from the behavior of traders, visitors throwing garbage, washing hands, not smoking in public places, and throwing saliva indiscriminately. The traders' activities are so dense that physical activities such as sports are rarely carried out by traders, which is an indicator of clean and healthy living behavior.Health support services in the initial examination of blood glucose for traders, will provide information to traders in traditional markets. When blood glucose gives an indication of whether a person has diabetes mellitus or not, it needs further examination.Based on the identification of the problems mentioned above, the priority problems that need to be solved are the knowledge and behavior of traders regarding clean and healthy living behavior in the market environment, and the lack of physical activity of traders needs to be carried out with an initial blood sugar check whenThe service method is by providing health education on clean and healthy living behavior in the market environment through booklet media. Initial blood glucose checks for traders in market environments use the POCT (Point of Care Testing) method, this method is widely used because it is easy and practical, the results of blood glucose tests can also be known in seconds and requires a small sample.This community service activity was carried out within five months, starting from the initial data collection, health education on clean and healthy living behavior, blood sugar checks while and evaluation of activities.The results obtained from 80 traders examined found 74 people (92.5%) blood glucose levels ≤ 200 mg/dl and 6 people (7.5%) blood glucose levels 200 mg/dl. Henceforth, it is hoped that traders who have blood glucose levels of less than 200 mg/dl will continue to maintain their health by managing their diet and physical activity and carrying out further tests to ensure DM occurs. as well as market management officers who always provide education to traders through the media booklet that has been given.